Atomistic understanding of cross-linking network in different epoxy resin: Effect of loop structure. (14th March 2022) - Zihan, Wang; Peibin, Kang; Tianyu, Wu; Dongli, Chen; Xiaoping, Yang; Gang, Sui
Abstract: Loops are the main component of the polymer crosslinked network. To understand and predict the structure and properties of epoxy resin, it is necessary to study the characteristics of loops in different epoxy systems. However, the identification of various loop structures in epoxy network is difficult due to multiple reaction sites of epoxy resins. Herein, molecular dynamics simulation (MD) was used to study the network structure of epoxy-amine system. A better way of classifying loop defects and loop structures was proposed. The shortest loop cycle around crosslink point was selected as the most likely loop structure of epoxy network and a new structural parameter, named ring efficiency, was introduced to assess the elastic contribution of the loops to the network. Based on this novel method, the comparison of structural and mechanical properties between different kinds of loop structures in epoxy network was successfully realized and it will be of great value in analyzing and predicting the crosslinked network characteristics of resin systems. Graphical abstract: Image 1 Highlights: The loop structure of epoxy-amine crosslinked system was investigated. The crosslinked structure was constructed by the distance-based modeling approach. Ring efficiency was proposed to characterize the feature of ring structure. The network structure with high ring efficiency had the good mechanical strength.